2015
DOI: 10.1155/2015/854621
|View full text |Cite
|
Sign up to set email alerts
|

Association between Programmed Cell Death 6 Interacting Protein Insertion/Deletion Polymorphism and the Risk of Breast Cancer in a Sample of Iranian Population

Abstract: It has been suggested that genetic factors contribute to patients' vulnerability to breast cancer (BC). The programmed cell death 6 interacting protein (PDCD6IP) encodes for a protein that is known to bind to the products of the PDCD6 gene, which is involved in the apoptosis pathway. The aim of this case-control study is to investigate the relationship between the PDCD6IP 15 bp insertion/deletion (I/D) polymorphism (rs28381975) and BC risk in an Iranian population. A total of 491 females, including 266 BC pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Some risk factors including early menarche, late menopause occurred, body mass index (BMI) and obesity after menopause, estrogen intake, alcohol consumption and tobacco use, exposure to ionizing radiation, and eating habits (3), as well as genetic (4)(5)(6), environmental factors (5,6), and ethnicity (7) can effect on the incidence of BC. In various studies, it was found that the serum levels of trace elements in patients with BC have changed and although their role is not fully understood, it may be associated with the risk of this disease (8).…”
Section: Introductionmentioning
confidence: 99%
“…Some risk factors including early menarche, late menopause occurred, body mass index (BMI) and obesity after menopause, estrogen intake, alcohol consumption and tobacco use, exposure to ionizing radiation, and eating habits (3), as well as genetic (4)(5)(6), environmental factors (5,6), and ethnicity (7) can effect on the incidence of BC. In various studies, it was found that the serum levels of trace elements in patients with BC have changed and although their role is not fully understood, it may be associated with the risk of this disease (8).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between miRNA-124-3p and PDCD6 was then verified using a dual Luciferase reporter assay system. PDCD6 is a calcium-binding modulator protein that regulates cell proliferation and death (23,24). Aberrant expression of PDCD6 has been observed in various types of human cancer and may act as either an oncogene or a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…2A). PDCD6 is a calcium-binding modulator protein, which regulates cell proliferation and apoptosis (23,24), indicating a promising role in CH development. Therefore, PDCD6 was used for subsequent experiments.…”
Section: Mir-124-3p Was Downregulated In Rats With Chmentioning
confidence: 99%
“…Ethical approvals for recruitment were taken from local Ethics Committee of Zahedan University of Medical Sciences, and informed consent was obtained from all patients and healthy individuals. The study design and enrolment procedure were described previously [29][30][31].…”
Section: Methodsmentioning
confidence: 99%